PROBLEMS OF THE IMPACT OF MODERNIZATION OF INDONESIA'S PUBLIC TRANSPORTATION EQUIPMENT SYSTEM - Tamrin Lamiri; Bambang Heri Supriyanto (Bajang Institute, 2023)
The problem with the modernization impact of Indonesia's public transportation system, the author chose this title because until now the modernization of the public transportation system in Indonesia, mainly with regard to the public transformation mode system, is still lacking due to several factors. The main problem in the article is to discuss how developments are, the factors that support the development of the modernization of the transportation system, efforts to overcome the adverse effects of modernization of the transportation system. The conclusion from the discussion is that the modernization of the transportation system makes a large contribution to the convenience of transportation, the factors that support the development of the modernization of the transportation system, namely the economy; geography, politics, defense and security, technology, competition and external (external) factors that affect the transportation mode system in Indonesia, including laws or government regulations, the influence of public service users, efforts to overcome the negative effects of modernizing the transportation system by implementing eco-principles -efficiency in meeting fuel needs, reducing motor vehicle exhaust fumes. The methodology used in this research is literature review research, which will use a descriptive research type with a literature approach, based on the existing reality.